2018
DOI: 10.3390/electronics7110304
|View full text |Cite
|
Sign up to set email alerts
|

Movement Detection with Event-Based Cameras: Comparison with Frame-Based Cameras in Robot Object Tracking Using Powerlink Communication

Abstract: Event-based cameras are not common in industrial applications despite the fact that they can add multiple advantages for applications with moving objects. In comparison with frame-based cameras, the amount of generated data is very low while keeping the main information in the scene. For an industrial environment with interconnected systems, data reduction becomes very important to avoid network congestion and provide faster response time. However, the use of new sensors as event-based cameras is not common si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(30 reference statements)
0
4
0
1
Order By: Relevance
“…Several authors deal with the comparison of event- and frame-cameras. Barrios-Avilés et al [ 5 ] test the object detection latency of event and standard cameras. Their vision system detects a black circular dot rotating on a white disk and estimates the position of the dot for control purposes.…”
Section: Related Workmentioning
confidence: 99%
“…Several authors deal with the comparison of event- and frame-cameras. Barrios-Avilés et al [ 5 ] test the object detection latency of event and standard cameras. Their vision system detects a black circular dot rotating on a white disk and estimates the position of the dot for control purposes.…”
Section: Related Workmentioning
confidence: 99%
“…Для керування такими засобами зазвичай використовують системи технічного зору, які здатні швидко і точно оцінити розташуванн навколишніх об'єктів у просторі та задавати нову траєкторію руху для уникнення зіткнень з завадами на своєму шляху. Серед таких систем можна навести цифрові камери так камери реєстрації подій (event-based cameras) [3,4]. Сучасні цифрові камери складаються з об'єктиву, що формує зображення в площині матричного фотоприймального пристрою та під'єднаного до нього цифрового сигнального процесору, який оброблює отриманні зображення.…”
Section: вступunclassified
“…The study highlighted the problems faced by standard optical flow algorithms such as Lucas-Kanade and local plane fit due to the noise in the event data stream and motion discontinuities. Event-based cameras in industrial robotics have recently become an active field of research [66]. In [66], the authors compared the performance of a 2-axis servo-controlled robot based on the data acquisition and motion tracking from an event camera and a framebased camera.…”
Section: B Event Camera-based Robotic Systems Controlmentioning
confidence: 99%
“…Event-based cameras in industrial robotics have recently become an active field of research [66]. In [66], the authors compared the performance of a 2-axis servo-controlled robot based on the data acquisition and motion tracking from an event camera and a framebased camera. The results showed that the robotic arm using the event-based camera could follow the object using image recognition while achieving up to 85% percent data reduction and providing an average of 99ms faster position detection than the frame-based camera.…”
Section: B Event Camera-based Robotic Systems Controlmentioning
confidence: 99%